Affinity of Serum Albumin and Fibrinogen to Cellulose, Its Hydrophobic Derivatives and Blends - Kargl, Rupert; Bračič, Matej; Resnik, Matic; Mozetič, Miran; Bauer, Wolfgang; Stana Kleinschek, Karin; Mohan, Tamilselvan (Frontiers in Chemistry, 2019)
This work describes the preparation of spin-coated thin polymer films composed of cellulose (CE), ethyl cellulose (EC) and cellulose acetate (CA) in the form of bi- or mono-component coatings on sensors of a quartz crystal microbalance with dissipation monitoring (QCM-D). Depending on the composition and derivative, hydrophilicity can be varied resulting in materials with different surface properties. The surfaces of mono- and bi-component films were also analyzed by atomic force microscopy (AFM) and large differences in the morphologies were found comprising nano- to micrometer sized pores. Extended protein adsorption studies were performed by a QCM-D with 0.1 mg mL-1 and 10 mg mL-1 bovine serum albumin (BSA) and 0.1 mg mL-1 and 1 mg mL-1 fibrinogen from bovine plasma in phosphate buffered saline. Analysis of the mass of bound proteins was conducted by applying the Voigt model and a comparison was made with the Sauerbrey wet mass of the proteins for all films. The amount of deposited proteins could be influenced by the composition of the films. It is proposed that the observed effects can be exploited in biomaterial science and that they can be used to extent the applicability of bio-based polymer thin films composed of commercial cellulose derivatives.